Penggunan E-Learning, E-Book, E-Journal dan Sistem Informasi Pendidikan Islam di Universitas Sriwijaya Palembang - Kasful Anwar Us; Mahdayeni Mahdayeni (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2019)
The 4.0 industrial revolution in the field of education, universities must be able to respond to this by carrying out reforms and reforms, especially Islamic tertiary institutions so as not to lag behind western education by conducting E-Learning-based education, E-Book E-Journal and Islamic Education Information System (SIMPE) which is a form of educational products nowadays that prioritize information technology. Responding to the development of education, Sriwijaya University (UNSRI) has implemented an E-Learning-based education system, E-Book E-Journal and Simpe in its education system. E-Learning, E-Book E-Journal and SIMPE is a global issue in the world of education today, especially in university education. For this reason, the author focuses on the Implementation of E-Learning, E-Book E-Journal and SIMPE conducted by the Sriwijaya University Palembang.